Wisdoms of humanity : Buddhism, paganism, and Christianity - Dubuisson, Daniel, 1950- (Leiden : Brill, 2011)
Resting on a new and long awaited comparative study (of buddhism, yoga, christian spirituality and ancient philosophies), this book restores wisdoms into their fascinating and vigorous personality. It particularly demonstrates that all of them were inspired by similar principles and conceived very comparable mental techniques.
A fragile and uncertain "I" -- A labile consciousness -- The pure consciousness of philosophers -- Impermanence and vacuity -- Unfinished humanity -- Techniques of the body and spiritual exercises -- Christian anthropology -- Disciplines of interior life -- Suffering and culpability -- Wisdoms and human sciences -- Metaphysics and religions -- Anthropology and wisdoms.
Includes bibliographical references and index.
Translated from the French.
Master record variable field(s) change: 072
Keywords: Wisdom -- Religious aspects -- Comparative studies; Wisdom -- Religious aspects; Religion; BODY, MIND & SPIRIT -- Inspiration & Personal Growth; BODY, MIND & SPIRIT -- Spirituality -- General; RELIGION -- Christianity -- General; RELIGION -- Devotional; RELIGION -- Spirituality; Wisdom -- Religious aspects; Electronic books; Comparative studies